Utilization of Milk Fish as A Basic Ingredient for Food Processed in Lembar Village, Lombok Barat District - Muhammad Zuhdi; Evi Ariani Sutomo; Ni Luh Vidya Wulandhari; Rujiatul Azmi; Winda Yuli Alfina; Qotrin Mujahidah; Safira Safira; Tina Sonia; Miftahul Rizkia Mulia Azani; Arrum Fitrianingsih; Yogi Saputra (Pascasarjana Universitas Mataram, 2023)
Milkfish is a type of fish that has good nutritional content for the human body and can be processed into any processed food, such as pilus amplang for milkfish. The reason for choosing milkfish as the basic ingredient for making pilus amplang is because most of the people in Lembar Village work as pond fishermen who have various types of fish, one of which is milkfish. The expected goal of this community service program is to be able to become an alternative in increasing the source of community income, as an effort in the forerunner of the emergence of Micro, Small and Medium Enterprises (MSMEs) and being able to increase the productivity of the people of Lembar Village. The method used in community service is through socialization and demonstration activities related to how to make milkfish amplang pilus to the people of Lembar Village, especially PKK mothers in Lembar Village, how to pack it, and market it properly